Mathematical Creative Thinking Ability of Junior High School Students in Solving Open-Ended Problem - Herwinanda Trisnaning Damayanti; Sumardi Sumardi (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2018)
The study aims to describe the ability of mathematical creative thinking on the aspects of fluency, flexibility, and originality in solving open-ended problem of Linear Equations with One Variable. The subjects are 7th grade students of one private junior high school in Surakarta, Central Java, Indonesia. The data was collected by the test, interview, and documentation. The method of data validation was used triangulation, i.e. techniques and resources. The analysis technique of the data was used an interactive method that consists of the reduction, presentation, and conclusion. The result of the research shows that the fluency aspect achieved by the students ability to mention the possibility of other answers. Then, the flexibility aspect is showed by the students use different method to solve the problem, or at least use the appropriate method. The originality aspect is showed by the students‘ ability to make the problem which are rarely found by other students.